The effect of conventional versus electronic cigarette use on treatment outcomes of peri-implant disease - Reham AlJasser; Mohammed Zahid; Mohammed AlSarhan; Dalal AlOtaibi; Saleh AlOraini (BMC, 2021)
Abstract Aim To compare changes in clinical periodontal parameters (gingival consistency, colour, BOP, PI, PD) and changes of salivary inflammatory biomarkers (IL-1 β, IL-6, MMP-8, TNF- α and TIMP-1 between conventional, electronic cigarette smokers and non-smokers after peri-implant treatment. Methods Study participants were grouped into three groups (i) Conventional cigarette smokers (ii) Electronic cigarette smokers and (iii) non-smokers respectively. A total of 60 adult patients aged (40-56 years) with 60 implants with active per-impantitis was included.Clinical and Biological parameters were evaluated before surgical treatment at baseline, one, six and twelve month post treatment. Pearson's chi-square test was used to compare the distribution of the categorical while Two-way repeated analysis of variance was used to compare the mean values of quantitative outcome variables among all study groups across the 4 time points. Results A total of 60 subjects (60 implants) were selected and classified into three groups as per their smoking method 20 participants in each group with one single targeted implant diagnosis with active peri-implantitis. The gingival colour, the change was statistically significant at one year of post treatment.The gingival consistency distribution across the three groups is not statistically significant at baseline, but it is statistically significant at one-month (p = 0.001), six months (p = 0.029) and at the completion of one-year (p = 0.018) post treatment. The plaque index of 100% of non-smokers had changed to '0' and 35% change in cigarettes and 30% change in electronic smokers which is statistically significant (p = 0.016).The prevalence of BOP was observed in the three groups as 72%, 76.5% and 88.9% at baseline. The mean values of PD have shown statistically significant change across the three groups over the four-time intervals of observation (p = 0.024). The comparison of mean values of IL-1 β, IL-6 and TIMP-1 has shown statistically significant change across the three groups over the four intervals of observation (p < 0.0001). Conclusions Electronic cigarette smoking was found to be most prevalent risk indicator for peri-implantitis. Compromised response of peri-implantitis treatment both clinically and biologically was found more among electronic cigarette smokers when compared to conventional cigarette smokers and non-smokers. Trial registration: This case-control study was conducted at King Saud University's Dental College, Riyadh, Saudi Arabia, in accordance with "Helsinki Declaration of Human Studies" and approved by the Institutional Review Board (Reference no: 87563).